2017
DOI: 10.1038/s41524-017-0034-y
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale structural signature of dynamic heterogeneities in metallic liquids

Abstract: With sufficiently high cooling rates, liquids will cross their equilibrium melting temperatures and can be maintained in a metastable undercooled state before solidifying. Studies of undercooled liquids reveal several intriguing dynamic phenomena and because explicit connections between liquid structure and liquids dynamics are difficult to identify, it remains a major challenge to capture the underlying structural link to these phenomena. Ab initio molecular dynamics (AIMD) simulations are yet especially powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The rather large difference in RDFs between the two compositions might also be anticipated from the relevance of the locally favored structures (bicapped square antiprisms) for the dynamics in these mixtures 94 . Furthermore, this anticipation is supported by a connection between decoupling of component dynamics, dynamical heterogeneity, and development of different local medium-range-like ordering in the supercooled regime for certain alloys where the local ordering is directly detectable in the RDFs 95 .…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The rather large difference in RDFs between the two compositions might also be anticipated from the relevance of the locally favored structures (bicapped square antiprisms) for the dynamics in these mixtures 94 . Furthermore, this anticipation is supported by a connection between decoupling of component dynamics, dynamical heterogeneity, and development of different local medium-range-like ordering in the supercooled regime for certain alloys where the local ordering is directly detectable in the RDFs 95 .…”
Section: Resultsmentioning
confidence: 90%
“…The quasiuniversality found in supercooled binary mixtures thus appears to be more subtle than the quasiuniversality observed in single-component atomic liquids at high temperatures. Future work should focus on clarifying the nature behind this observation in the supercooled regime which could be related to local orderings in the supercooled liquid 95 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For liquid metals and alloys changes in the dynamics within the equilibrium liquid state have been reported. Violations of the Stokes-Einstein relation in experiment 37 and MD-simulations have been reported 10 and linked to the onset of correlated particle movements 12 14 , 38 . The diffusion coefficients for a wide range of glass forming liquids was investigated, including 11 alloys, and an Arrhenius crossover was reported at a temperature deep in the liquid state of alloys at about 39 , a temperature range compatible with our estimate for liquid aluminium.…”
Section: Discussionmentioning
confidence: 95%
“…It was suggested that this slow process is responsible for the freezing of the liquid and was later confirmed experimentally 8 , 9 . Further MD-simulations on binary alloys found changes in the dynamics far above the glass transition temperature and sometimes even far above the liquidus, which were related to dynamic heterogeneity and the onset of collective particle movements 10 – 14 .…”
Section: Introductionmentioning
confidence: 98%